Estudo da produção enzimática de biodiesel utilizando óleo residual e etanol - Costa Filho, Edilson Holanda (2008)
Biodiesel is a mixture of fatty acid alkyl esters produced by the reaction between vegetable oils and short chain alcohols, like methanol and ethanol, using a catalyst that can be acid, basic or enzymatic. However, the high cost of the raw material when refined vegetable oil is used, have made biodiesel production economically unattractive. Therefore, research with waste oils has increased, showing the technical viability of the production of biodiesel using the residential and industrial residues as raw material. Another variable that has influenced this type of reaction is the type of alcohol. In Brazil, the use of ethanol is interesting because the country has become one of the top worldwide producers of ethanol from vegetables sources, a cheaper and less toxic product than methanol, decreasing our petroleum dependence. The type of catalyst also influences biodiesel production. Alkali is the catalysts that is more often used in industry, but when the vegetable oil has a high acid value, it can not be used because soap is produced, diminishing the esters yield. In this case an acid or an enzyme is used as a catalyst. Based on the previous explanation, the results of this work correspond to the study of enzymatic production of biodiesel using waste oil and ethanol. The immobilized Candida antarctica lipase (Novozym 435) behavior was studied in the oleic acid esterification, studying the effect of the variables that has influence in the process. The variables chosen were: temperature (30 – 50oC), molar ratio acid:alcohol (1:1 – 1:6) and water content (0 – 20%). The reaction were performed in closed reactors with a capacity of 250 mL containing 10 g of oil, a known amount content of alcohol, pre-determined by experimental design and enzyme content of 5% p/p, based on the oil mass. The reaction medium was kept under constant stirring, 200 rpm. Maximum conversion of 88,36% was achieved when high molar ration, the lower temperature and water content values were used. However, by the kinetic study, it can be concluded that it is not necessary to use an alcohol excess to achieve good conversions. After that, the behavior of Candida Antarctica lipase B immobilized in chitosan was studied in acid oleic esterification. A slower initial rate of reaction was observed in comparison to Novozym 435. The behavior of both lipases was also studied in the esterification of waste coconut oil, showing good stability and giving a conversion of about 80% in 60 minutes. Both biocatalyst could be reused 10 times, keeping the same activity. In order to compare the behavior of Novozym 435 in two different mediums, an experimental design was performed with waste cotton oil, which had a low acid value. The same negative influence of the temperature and molar ratio was observed, but with a high reaction time, getting a maximum conversion of 82,66% in 72 hours of reaction. To calculate the conversions, the decreasing of the acid value was used when the raw material had a high acid value, and when the raw material had a low acid value the glycerol production was used.